A comparison of different approaches for depth profiling of films and coatings by confocal Raman microscopy - Miguel, María de la Paz (2012)
We compare and analyze different approaches to perform depth profiling of polymer films and coatings by confocal Raman microscopy (CRM). Data were generated using three methodologies: conventional metallurgical objectives, oil-immersion optics and numerical post processing of the as-measured intensity profiles, via an optimized deconvolution technique adapted to CRM. A series of bi- and multi-layered polymeric films were used as test systems. Strengths and weaknesses of each methodology are evaluated in terms of delivered depth resolution, signal throughput and flexibility. It is shown that the application of regularized deconvolution on data obtained from dry objectives yielded intensity profiles with a quality comparable, in some cases superior, to those obtained with immersion objectives, with the advantage of being totally non-invasive. © 2011 Elsevier B.V. All Rights Reserved.